The Cyclically Seasonal Drosophila subobscura Inversion O7 Originated From Fragile Genomic Sites and Relocated Immunity and Metabolic Genes - Karageorgiou, Charikleia; Tarrío, Rosa; Rodríguez-Trelles, Francisco (Frontiers in Genetics, 2020)
Chromosome inversions are important contributors to standing genetic variation in Drosophila subobscura. Presently, the species is experiencing a rapid replacement of high-latitude by low-latitude inversions associated with global warming. Yet not all low-latitude inversions are correlated with the ongoing warming trend. This is particularly unexpected in the case of O7, because it shows a regular seasonal cycle that peaks in summer, and rose with a heat wave. The inconsistent behavior of O7 across components of the ambient temperature suggests that is causally more complex than simply due to temperature alone. In order to understand the dynamics of O7, high quality genomic data is needed to determine both the breakpoints as well as the genetic content. To fill this gap, here we generated a PacBio long read-based chromosome-scale genome assembly, from a highly homozygous line made isogenic for an O3+4+7 chromosome. Then we isolated the complete continuous sequence of O7 by conserved synteny analysis with the available reference genome. Main findings include: i) The assembled O7 inversion stretches 9.936 Mb, containing >1,000 annotated genes. ii) O7 had a complex origin, involving multiple breaks associated with non-B DNA-forming motifs, formation of a microinversion, and ectopic repair in trans with the two homologous chromosomes. iii) The O7 breakpoints carry a pre-inversion record of fragility, including a sequence insertion, and transposition with later inverted duplication of an Attacin immunity gene. And iv) the O7 inversion relocated the major insulin signaling forkhead box subgroup O (foxo) gene in tight linkage with its antagonistic regulatory partner serine/threonine-protein kinase B (Akt1), and disrupted concerted evolution of the two inverted Attacin duplicates, reattaching them to dFOXO metabolic enhancers. Our findings suggest that O7 exerts antagonistic pleiotropic effects on reproduction and immunity, setting a framework to understand its relationship with climate change. Furthermore, they are relevant for fragility in genome rearrangement evolution, and for current views on the contribution of breakage versus repair in shaping inversion-breakpoint junctions.